Robot based on task-space dynamical model (2011)
This study deals with the dynamic modelling and task space control of the Stewart-Gough platform. The dynamic equations were obtained using the virtual work approach, and include all the 13 presented in the platform, that is, two bodies per each leg and the upper ring. The results show some similarities in the dynamic model of serial and parallel robots, making it possible to extend the control theory of serial robot to the Stewart-Gough platform. To show this, an adaptive control law is proposed to control the parallel platform. The law is obtained from the dynamical equation and its performance is tested using a sinusoidal path for position and orientation of the upper ring of parallel robot. Some additional simulations are carried out to demonstrate a well-behaved controller. © 2011 The Institution of Engineering and Technology.